Photovoltaic Solar Energy in Forest Nurseries: A Strategic Decision Based on Real Options Analysis - Rocha, Qüinny Soares [UNESP]; Munis, Rafaele Almeida [UNESP]; da Silva, Richardson Barbosa Gomes [UNESP]; Aguilar, Elí Wilfredo Zavaleta [UNESP]; Simões, Danilo [UNESP] (MDPI, 2023)
With the growing demand for investment projects in renewable energy, it is essential for the economic feasibility analysis to consider the inherent uncertainties of these projects and enable more accurate investment decisions. In this way, we analyze whether investment projects in photovoltaic panels to produce electrical energy in a forest nursery are economically viable through the analysis of real options. We consider the energy demand of a forest nursery with an initial investment of USD 90,417 in photovoltaic panels. The managerial flexibilities of deferral, expansion of 30.0% of the energy production capacity, and the project’s abandonment were inserted into the binomial model of the decision tree, built in discrete time. The project’s expanded net present value was 79.2% higher than the traditional net present value, capturing the value of flexibilities for managers. The deferral option was the one that most impacted the expanded net present value. Investment projects in photovoltaic panels to produce electricity in a forest nursery are economically viable when analyzed through real options.
Keywords: cuttings; Eucalyptus; managerial flexibilities; net present value; photovoltaic panels; renewable energy